2015
DOI: 10.1017/thg.2015.57
|View full text |Cite
|
Sign up to set email alerts
|

Zygosity Differences in Height and Body Mass Index of Twins From Infancy to Old Age: A Study of the CODATwins Project

Abstract: A trend toward greater body size in dizygotic (DZ) than in monozygotic (MZ) twins has been suggested by some but not all studies, and this difference may also vary by age. We analyzed zygosity differences in mean values and variances of height and body mass index (BMI) among male and female twins from infancy to old age. Data were derived from an international database of 54 twin cohorts participating in the COllaborative project of Development of Anthropometrical measures in Twins (CODATwins), and included 84… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 69 publications
2
26
0
1
Order By: Relevance
“…However, these sources of bias are unlikely to explain our main result, i.e., relatively similar heritability estimates of adult height over birth cohorts. Finally, since we previously showed that there was no zygosity difference in height variance (Jelenkovic et al, 2015), variance components estimates should not be affected by changes in the proportion of MZ to DZ twins across birth-year cohorts.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, these sources of bias are unlikely to explain our main result, i.e., relatively similar heritability estimates of adult height over birth cohorts. Finally, since we previously showed that there was no zygosity difference in height variance (Jelenkovic et al, 2015), variance components estimates should not be affected by changes in the proportion of MZ to DZ twins across birth-year cohorts.…”
Section: Discussionmentioning
confidence: 92%
“…The ACE sex-limitation model was selected as a starting point of the univariate modeling based on the following criteria: (i) MZ within-pair correlations were clearly higher than DZ correlations consistent with the influence of genetic effects, (ii) the magnitude of the difference between MZ and DZ correlations (rDZ > 1/2 rMZ) indicated the presence of common environmental effects and (iii) the lower within-pair correlations for OSDZ than for SSDZ twins observed for most birth-year groups suggested the presence of sex-specific genetic effects (results not shown). Previous findings from this international database showed that both male and female DZ twins are slightly taller than MZ twins in these age groups (Jelenkovic et al, 2015), and thus different means for MZ and DZ twins were allowed. The fit of the univariate models for height at each birth-year group is shown in Supplementary file 1B.…”
Section: Methodsmentioning
confidence: 99%
“…Previous findings from this international database showed that both male and female DZ twins have greater height than MZ twins in these age groups46, and thus different means for MZ and DZ twins were allowed. The fit of the univariate models for height at each one-year age group is shown in Supplementary Table S2.…”
Section: Methodsmentioning
confidence: 99%
“…It is also not very likely that physiological features related to twin pregnancies would be the explanation. MZ twins are somewhat lighter at birth (Hur et al, 2005) and slightly shorter in adolescence and adulthood than DZ twins (Jelenkovic et al, 2015). Low birth weight has been found to be associated with slower cognitive development (Broekman et al, 2009) and short stature in adulthood with lower IQ (Silventoinen et al, 2006) and less education (Magnusson et al, 2006).…”
Section: Discussionmentioning
confidence: 99%